Peran Kelompok Sebaya Dalam Pendidikan Nonformal (Peer Support) Untuk Meningkatkan Motivasi Belajar Siswa SMK Dari Keluarga Disfunsional - Fitri Angraini; Decky Avrilianda (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
Students of vocational high schools (SMK) from dysfunctional families often experience learning motivation problems, such as low self-confidence and lack of courage to participate actively. This study aims to describe the forms of peer support in non-formal education and to explain the role of peer group interaction in enhancing learning motivation among SMK students from dysfunctional family backgrounds. This research employed a qualitative approach with a case study design. The participants consisted of students from dysfunctional families, peers, and a school counselor. Data were collected through observation, in-depth interviews, and documentation conducted outside formal learning hours. The findings indicate that peer support in non-formal education is manifested through emotional, informational, instrumental, and appraisal support. Flexible and egalitarian peer interactions contribute to students’ sense of acceptance, increased self-confidence, and greater willingness to engage in learning activities. These results highlight the importance of non-formal education as a supportive space for improving learning motivation among students from dysfunctional families.